2018
DOI: 10.1186/s12917-017-1318-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute-onset high-morbidity primary photosensitisation in sheep associated with consumption of the Casbah and Mauro cultivars of the pasture legume Biserrula

Abstract: BackgroundPrimary photosensitisation (PS) subsequent to ingestion of the pasture legume Biserrula pelecinus L. (biserrula) has recently been confirmed in grazing livestock. Given the potential utility of this pasture species in challenging climates, a grazing trial was undertaken to examine if both varieties ‘Casbah’ and ‘Mauro’ were able to cause photosensitisation in livestock, and if this could be mitigated by grazing in winter, or in combination with other common pasture species.ResultsA controlled grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Similar to previous findings, in this survey, more than half of the veterinary respondents rated secondary (hepatogeneous) photosensitisation as the most common type of photosensitisation, further supporting previous evidence that hepatogeneous photosensitising plants or agents are significantly more common than those containing primary photocytotoxic compounds 1,7 . Reasons for this commonality of presentation are that toxic plants know to contain hepatotoxic agents are found more frequently in nature than those containing primary sensitisers 8,9 . Equally, the least common type of photosensitisation, the congenital type (II) that requires specific genome mutations, is very uncommon in livestock 10,11 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to previous findings, in this survey, more than half of the veterinary respondents rated secondary (hepatogeneous) photosensitisation as the most common type of photosensitisation, further supporting previous evidence that hepatogeneous photosensitising plants or agents are significantly more common than those containing primary photocytotoxic compounds 1,7 . Reasons for this commonality of presentation are that toxic plants know to contain hepatotoxic agents are found more frequently in nature than those containing primary sensitisers 8,9 . Equally, the least common type of photosensitisation, the congenital type (II) that requires specific genome mutations, is very uncommon in livestock 10,11 .…”
Section: Discussionsupporting
confidence: 89%
“…1,7 Reasons for this commonality of presentation are that toxic plants know to contain hepatotoxic agents are found more frequently in nature than those containing primary sensitisers. 8,9 Equally, the least common type of photosensitisation, the congenital type (II) that requires specific genome mutations, is very uncommon in livestock. 10,11 The relative commonality of secondary photosensitisation is increased compared to other presentations as hepatobiliary impairment resulting in secondary photosensitisation can also be caused by other agents such as hepatotoxic toxins in fungal contaminants in feed, infectious or inflammatory liver disease, liver parasites, metabolic disease, copper accumulation, or neoplasia, all of which could results in secondary symptoms of photosensitisation.…”
Section: Common Causative Agentsmentioning
confidence: 99%
“…Australia has experienced outbreaks of primary photosensitisation that are specific and unique to this region. One examples is photosensitisation caused by the pasture legume Biserrula pelecinus , although a native of the southern Mediterranean, it is exclusively used as a livestock fodder only in Australia [102] where this pasture legume is now clearly identified as causing outbreaks of primary photosensitisation [37,38]. Outbreaks that have never been recorded in its native domains where it grows as a native only in mixed swards.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, no objective photosensitisation scoring protocol had been defined in literature resulting in prevalence and severity of affected animals to be hard to compare between outbreaks. Recently, a semi-objective photosensitisation grading system has been developed for sheep to address this issue [37]. The use of such a grading system in future outbreaks will allow better correlation between access to potentially photosensitising pastures or feedstuffs with more accurate determination of the timing of onset of outbreaks, as well as a more definitive and consistent identification of the severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…However, many recent studies revealed that Streptococcus dysgalactiae subsp. equisimilis can cause various soft-tissue infections and occasionally more serious infections including neonatal sepsis, bacteremia, endocarditis, meningitis, peritonitis and arthritis [ 21 , 22 ]. In horses, Streptococcus dysgalactiae subsp.…”
Section: Discussionmentioning
confidence: 99%